Anti-Bacterial and Anti-Fungal Activities of Citrus sinensis Leaves Extracts - Mohammed, Nasiru; Sanyinna, Yusuf Muhammad; Ahmed, Ridwan Nuhu (International Journal of Scientific Research in Biological Sciences, 2021)
The biological activities and medicinal benefits of different plants have been long known. Therefore, humans have ever since researched, tried and utilised them for their betterment. In the present study, an effort was made to perceive the existence of microbial infections alongside with herbal remedy of these infections. The aim of this study was to determine the anti-bacterial and anti-fungal activities of Citrus sinensis leaves extracts. In vitro anti-bacterial and anti-fungal potentials of Citrus sinensis leaves extracts were investigated. Four different solvents i.e. ethanol, ethyl acetate, petroleum ether and water were used for extract preparation from the plant leaves. The anti-microbial activity potency of leaves extracts was evaluated by Standard Kirby-Bauer Disk Diffusion Method against reference strains of Staphylococcus aureus, Staphylococcus epidermidis, Escherichia coli, Salmonella typhi, Aspergillus niger and Aspergillus fumigatus. Four different concentrations (2000 µg, 1000 µg, 500 µg and 200 µg) of each extract were investigated against the test organisms. Significant anti-bacterial activity was displayed by ethanol and ethyl acetate extracts against Escherichia coli (ATCC 25922). No activity was displayed by petroleum and aqueous extracts at all concentrations. A significant anti-bacterial activity was displayed against Salmonella typhi (ATCC 14028). No activity was displayed by ethyl acetate extract except at 1000 µg. There was no activity displayed by all the extracts against Staphylococcus aureus (ATCC 25923) and Staphylococcus epidermidis (ATCC 12228) at all concentrations. Ethanol extract displayed an exceptional anti-fungal activity against Aspergillus niger (ATCC 16404) and Aspergillus fumigatus (ATCC 16404). No activity was displayed by aqueous extract at all concentrations. This study justifies the claimed uses of Citrus sinensis leaves extracts in the Pakistan’s traditional system of medicine to treat various diseases. The results of this study show the extracts to possess significant antibacterial and antifungal activities to leaves extracts of Citrus sinensis, and are considered appropriate for empirical treatment of various diseases in the study area. It is therefore, recommended that further studies of these extracts should be carried out by agar well dilution and other methods prepared in different solvents and evaluated again through in-depth analysis by fractionation, structure elucidation and docking studies.